Effect of Volumetric Fraction of Samia ricini Silk Fiber Ribbon in Fiber-Reinforced Composite Material on Water Absorption - Paramarta, Sagita Pradnya; Sunarintyas, Siti; Irnawati, Dyah (Journal Center of Excellent : Health Assistive Technology, 2025)
Background: Fiber is added to composite resin with the aim of increasing strength. The strength of composite resin is influenced by water absorption. Samia ricini silk fiber has semihydrophilic properties which can affect water absorption in FRC. One of the ways FRC water absorption is influenced by volumetric fraction. Objective: to determine the effect of the volumetric fraction of Samia ricini silk fiber ribbon in FRC on water absorption. Method: The materials used in this research were flowable composite resin and Samia ricini fiber. The samples were made into 3 groups with varying volumetric fractions of 0%, 25% and 50%, with each group having 6 samples. The sample was then weighed to an accuracy of 0.0001 g, then soaked in water for 7 days in an incubator. After 7 days, weighing was carried out again to calculate the weight percentage of water absorption in the FRC. The data obtained was then analyzed using One Way ANOVA. Results: This research show that water absorption has increased in line with the increase in volumetric fraction. The percentage of water absorption in the volumetric fractions of 0%, 25%, and 50% respectively is 0.5298 ± 0.1190%, 0.8430 ± 0.3191%, and 0.9382 ± 0.4215%. The results of the One Way ANOVA analysis show F = 2.798 with a significance of 0.093 so that the three volumetric fraction groups do not have significant differences. Conclusion: Volumetric fraction does not significantly influence the water absorption of composite resin during 7 days of immersion.